World Beliefs and Cultures : Christianity - Sue Penney (Chicago, IL, United States Heinemann Educational Books, 2007)
"What holy texts do Christians have in common with Jews? Why is the fish a symbol of Christianity? How did eggs become an important Easter symbol? Discover the rich cultural background behind this major world religion. Find out where Christianity originated, trace its history, and explore the meanings of its symbols. Explore Christian holy books and religious teachings. Learn about major festivals, celebrations, and rites of passage. Meet young people from around the world who share their reflections about Christianity."
Keywords: Non Fiction